Генріх Вальтер і Україна - Melnik, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2002)
The life of eminent German botanist and ecologist Heinrich Walter (1898-1989) is described. Scientific achievements o f H. Walter are estimated. His contribution in the study of flora of Ukraine are elucidated.